2013
DOI: 10.5888/pcd10.120295
|View full text |Cite
|
Sign up to set email alerts
|

Family Child Care Providers’ Compliance With State Physical Activity Regulations, Delaware Child Care Provider Survey, 2011

Abstract: IntroductionDelaware is one state that has implemented comprehensive child care regulations to foster healthy dietary and physical activity behaviors of young children. This study describes the Delaware family child care environment and providers’ knowledge of and compliance with physical activity regulations. We analyzed the data to determine characteristics associated with predictors of knowledge of and compliance with these regulations.MethodsA random stratified sample of 663 licensed Delaware family child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Our analysis showed that factors such as classroom size, operating hours, and teaching staff turnover were associated with regulatory compliance. Consistent with the previous findings, our analysis showed that participation in CACFP was associated with better compliance with regulations related to nutrition ( 12 ) and that compliance with regulations related to physical activity was associated with the presence of physical activity facilities at the center ( 11 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our analysis showed that factors such as classroom size, operating hours, and teaching staff turnover were associated with regulatory compliance. Consistent with the previous findings, our analysis showed that participation in CACFP was associated with better compliance with regulations related to nutrition ( 12 ) and that compliance with regulations related to physical activity was associated with the presence of physical activity facilities at the center ( 11 ).…”
Section: Discussionsupporting
confidence: 90%
“…Few empirical studies have systematically assessed compliance with regulations concerning nutrition and physical activity in child care settings. Recent assessments of compliance with nutrition and physical activity regulations among child care centers in Delaware found that 86% of child care centers were compliant with state-wide recommendations (not regulations) regarding unstructured physical activity and 78% compliant with the recommendations concerning structured physical activity ( 11 ). These findings are consistent with ours: 77.5% of centers were compliant with the regulations regarding structured physical activity and 85.5% of centers were compliant with the regulation concerning total physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Best-practice guidelines recommend that staff receive PA training at least twice per year (23). A previous study in Delaware of family childcare providers reported that 86% had PA training in the last 12 months, compared with 43% of licensed childcare providers (8). In the present study, only 30% (home) and 21% (licensed) of respondents had this training in the last 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, the childcare PA environment has been characterized using statespecific surveys in Washington, Oklahoma, and Delaware (8)(9)(10). Similar studies in other states are necessary because licensing guidelines, weather, beliefs, and practices vary (11,12).…”
Section: Introductionmentioning
confidence: 99%